(untitled) (Alternautas, 2022)
Over the past months the Caribbean island of Puerto Rico has experienced one of the worst droughts in years. The country has been suffering for a while a progressive worsening of the quality, availability and distribution of water. The local press has argued that a "rainfall deficit" is the cause of the problem. The drought is presented as a "natural" and "administrative-technical" problem (read: apolitical), which can be remedied with larger and more "efficient" infrastructure and management of the supply system. In this article the author examines more closely the reasons why these problems of planning and the management of water are so persistent. He suggests that they are rooted in the political-economic system of Puerto Rico. From this perspective, planning in Puerto Rico has successfully encouraged the accumulation of capital in certain sectors, but not the common wellbeing and sustainability. On the other hand, traditional solutions based on the construction of infrastructure, which respond to the logic of this model (capitalist developmentalism), have also failed. In order to confront this situation it is necessary to transform these traditional schemes and start to conceptualize water as a common good that must be managed collectively for the well-being and sustainability of the population.